[Londrangar Lava Flows and Coast of Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of londrangar lava flows and the coast of Snæfellsnes Peninsula. The dark cliffs to the left were covered in a grass layer and piles of dark rock. A black lava rock platform sits along the blue water to the right. Two people in orange walk along the cliffs to the left.